PERAN PEMERINTAH DALAM PEMBANGUNAN JALAN LINTAS SEKAPAS-SEKELADI KABUPATEN ROKAN HILIR TAHUN 2022-2023 - Sari, Yanofita; Hadi, Syofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The role of government is very important in designing and facing economic development problems. The size of the government's role determines how these problems are resolved. Development is a process of advancing or improving conditions through various stages in a planned and sustainable manner which aims to change people's lives towards better change. The problem in this research is the lack of good road access and the lack of local government commitment in building the Sekapas to Sekeladi road. The purpose of this research is to determine the implementation of the construction of the Sekapas-Sekeladi causeway in Rokan Hilir Regency and determine the factors inhibiting the construction of the Sekapas-Sekeladi pass by referring to the Government Management theory according to Purnamasari, Hanny, Ramdani, 2018, namely Government Planning, Organizing, Actuanting and Controlling. This research is a qualitative descriptive research with the main data sources in the form of primary data and secondary data. The data collection techniques used were interview and documentation techniques. This data analysis technique is Data Reduction, Data Presentation and Conclusion Drawing. The results of this research are that the road construction process in Sepakapas-Sekeladi Village has not been carried out well due to several inhibiting factors, namely natural disasters such as floods, insufficient budget and lack of supervision from the government in implementing it. construction of this causeway. Keywords: Planning, Organizing, Actuanting, Controlling